Comité editorial y científico - Mora Delgado, Jairo (Revista Agroforestería Neotropical, 2020)
Comité Científico Internacional Eduardo Somarriba (CATIE, Costa Rica) Cristina Goldfarb (INTA, Argentina) Guillermo Navarro (EARTH, Costa Rica) Fabio Messa (Fundación Polar, Venezuela) José Gobbi (INTA, Argentina) Raúl Ramos (INIAP, Ecuador) Miguel Godino (Universidad Politécnica de Madrid) Comité Editorial Jairo Mora-Delgado, PhD. (Universidad del Tolima) Hernán Jair Andrade, PhD. (Universidad del Tolima) Jorge Navia, PhD. (Universidad de Nariño) Héctor Fabio Libreros, PhD. (Universidad del Tolima) Luis Alfonso Giraldo, PhD. (Universidad del Nacional -Medellín) Vladimir Sánchez, M.Sc. (Universidad de los Llanos) Rosven Arévalo, PhD. (Universidad del Tolima) Mario J. Gómez, M.Sc (Universidad del Tolima) Julián Estrada, PhD. (Universidad del Caldas) Isaías Tobasura, PhD. (Universidad de Caldas) Alexander Navas, M.Sc. (Universidad de la Salle) Marco Heli Franco, PhD (Cand) (Universidad Nacional- Bogotá) Ricardo Malagón, M.Sc (Universidad Nacional-Palmira)